Analysis Of Ta’awun Fund Model Best Practice From Indonesia - Jaenudin, Dindin; Firdaus, Achmad; M. Afendi, Farit; Possuma, Bayu Taufiq (Universitas Islam Negeri Raden Intan Lampung, 2018)
The Muslim population of Indonesia in 2010 reached 207 million, while the number of poor people reached 27,76 million. On the other hand, Indonesia is prone to natural disaster. By 2015 there are 16,830 villages hit by floods, 3,827 villages experiencing earthquakes, and 7,861 villages experiencing landslides. It is important for Indonesian people to pool fundraising to help each other (ta'awun). One of the schemes is through the microtakaful program. The next issue is the inability of the poor Indonesian to pay a pooling fund. The research is conducted with the aim to analyze the appropriate model of microtakaful in Indonesia using infaq/sadaqah and zakah fund as an alternative payment of subsidy of microtakaful contribution. The research is conducted with several methods, namely the study of in-depth literature on the utilization of infaq/sadaqah and zakah fund. The proposed models of utilization of infaq/sadaqah and zakah fund to subsidy ta’awun fund, validate the model through interviews to experts, practitioners and fund managers, process the data through Analytic Network Process (ANP), and determine the best model in utilizing infaq/sadaqah and zakah fund to subsidy ta’awun fund. Fund management model to become the object of research are microtakaful model and subsidy fund from the government model. The study shows that: Firstly, Ta'awun's fundraising in Indonesia is in line with the shariah objectives of protecting the soul, protecting religion, protecting intellect, protecting wealth, and protecting progeny. Secondly, the microtakaful model implemented in Indonesia is a microtakaful model by institution independently, a microtakaful model with a subsidy from infaq/sadaqahfund, a microtakaful model with a subsidy from zakah funds, ta’awun fund management model with a subsidy from the government and microtakaful model with a subsidy from other institution. Third, an important component in microtakaful is aqad, participant, underwriting process, investment, donor party and facility needs. The proper aqad in ta’awunfundraising is mudharabahmusytarakah.The simple Underwriting process is required. Parties that act as donors are zakah institution and government. Participants as beneficiaries of the contribution are poor and needy. Keywords : Microtakaful, Ta'awun, Zakah, Infaq, Sodaqah